Avian species composition and ecological distribution in south lake wetland park, hohhot (Mongolian Journal of Agricultural Sciences, 2017)
Species diversity and composition of bird community at South Lake Wetland Park in Hohhot city were investigated from October 2013 to September 2014. In total，64 bird species belonging to 33 families and 14 orders were recorded. There are 36 summer migrant species, 15 resident species, 11 traveling species and 2 winter migrant species found. The habitats of birds were grouped into four types (wetland, woodland, grassland and residential area) according to topography and vegetation types in the survey area．Shannon-Weiner Diversity Index (H`) was 2.9450 in wetland area and 1.0768 in grassland area the highest and the lowest values, respectively. The evenness of bird species was 0.4058 lowest in woodland and 0.7581 highest in residential area. The dominance index of bird species was 0.0733 lowest in the wetland and 0.4319 highest in the woodland, respectively. This paper analyzed the relationship between the main dominant bird species and their habitat characteristics，explained the main reasons for the increased bird species number.